From classroom to industry: Entrepreneurship students' perceptions of a subject-based open innovation challenge - Donaldson, Colin (The international journal of management education, 2025)
Studies emphasize the positive and enriching impact provided by open-ended learning experiences delivered in authentic settings and that aim to solve real problems faced by industry actors. However, further research is needed to understand how students perceive these challenges, as not all aspects of their learning experience may be viewed positively. This study explores students' perceptions of their experiences participating in an open innovation challenge grounded in problem-based learning. The reflections of 33 Business Administration and Entrepreneurship students were qualitatively analyzed through a content-driven inductive coding process informed by the Gioia method. The analysis revealed three aggregate dimensions comprising eight sub-themes of student perceptions. Findings highlight both positive and negative aspects with some sub-themes displaying ambivalent effects. This study contributes to the literature on education-related industry-university collaboration providing a nuanced understanding of students' perspectives on problem-based learning challenges. It addresses a research and practice gap on the teaching mission of higher educational institutions and their responsibility to align educational goals with students' professional aspirations. •Forging links between industry and higher educational institutions has been a longstanding strategic imperative.•Limited emphasis has been placed on student perceptions of their experiences.•Student experiences can be positive, negative or ambivalent.